Концепція управління збалансованим розвитком промислових підприємств - Коверга, С.В. (Економіка промисловості, 2014)
Проаналізовано існуючі наукові та практичні підходи до управління збалансованим розвитком промислових підприємств, визначено їх недоліки. Систематизовано способи виявлення дисбалансів, основні заходи і цілі, пов’язані зі збалансованим розвитком. Запропоновано концептуальну схему управління збалансованим функціонуванням і розвитком підприємства. Проанализированы существующие научные и практические подходы к управлению устойчивым развитием промышленных предприятий, определены их недостатки. Систематизированы способы выявления дисбалансов, основные мероприятия и цели, связанные с устойчивым развитием. Предложена концептуальная схема управления сбалансированным функционированием и развитием предприятия. The development of the economy of Ukraine and manufacturing enterprises in particular is characterized by the change of tendencies, absence of the strict order and predomination of the crisis over the stable development. The situation can be described as “the system imbalance”. It is the proof that scientific researches that are devoted to the management of the balanced development of manufacturing enterprises are up-to-date. The research of theoretic, scientific and practical provisions as to the management of the balanced development of manufacturing enterprises as a whole and the increase of the balance of certain aspects of the operation of manufacturing enterprises in particular demands to arrange the main theoretic and methodic preconditions to create the unique system. Thus, it is necessary to set up the unique concept of the management of the balanced development of manufacturing enterprises. The objective of the article is the development of the concept of the management of the balanced operation and development of manufacturing enterprises.The available scientific and practical approaches to the management of the balanced development of manufacturing enterprises are studied, their disadvantages are determined. It is proved that the estimation of the imbalance is always subjective (even if it is set in the framework of a certain scientific paradigm, theoretic or practical approach) and the viewpoint of the observer and his aims influence the setting of such an estimation.It is mentioned that the balance of an economic system can be defined as a measure of conformity of the characteristics of one element of a system to the demands of the other elements of the system and also of the characteristics of the system to the objects of the environment that results in promoting the achievements of an objectives and criteria of the operation and development of a system.The specification of such notions as “causes”, “instances”, “consequences” of the imbalance is offered. The methods of uncovering the cases of the imbalance, main measures and objectives that are related to the balanced development are classified.Instances of the balance (the extent of the conformity of the subjective and objective demands and requirements, the extent of resources endow, the extent of the correlation accuracy, and the extent of sufficiency to meet an aim) are given. The concept model of the management of the balanced operation and development of the enterprises is suggested.